Money Price Relationship under the Currency Board System: The Case of Argentina - Selahattin Togay; Nezir Kose (Turkish Economic Association, 2009)
In this study, the endogenous money hypothesis is examined for the Argentinean economy employing exogeneity tests by using monthly data for the time period 1991-2001 within the frame of money and price relationship in a Currency Board-like system. Empirical results support the hypothesis which suggests that money supply is endogenous.
Keywords: C12; C22; E51; E58; 330; Currency Board; Argentina; Money Supply Endogeneity; Exogeneity Test; Geldmenge; Currency-Board-System; Argentinien